Adolescent alcohol use and mental health : is there a gender difference? - Birta Rún Benediktsdóttir 2001-; Tara Sif Þrastardóttir 1986- (2023)
In this study, Icelandic secondary school students' alcohol use and mental health were examined. Additionally, gender differences between and alcohol use and mental health was examined. Previous research on adolescent alcohol consumption related to gender differences has produced inconsistent results. While some studies have found that boys consume more alcohol than girls, others have found the exact opposite. Regarding gender differences in the relationship between mental health and alcohol use, previous studies have repeatedly shown that alcohol consumption has a stronger relationship with mental health among girls than boys. For the analysis of this study, data from the survey Youth in Iceland 2018 were used. Among participants were 1001 boys (50.6%), 962 girls (48.6%), and 15 students (0.8%) who did not declare their gender. The main results were that 56.1% of girls and 47.0% of boys, reported they have been drunk at least once in their lifetime. Depression, anxiety and self-esteem were all significantly associated with alcohol use for females, however, a significant association was not found for males. Only one variable was significantly associated with alcohol use for males, which was parental financial situation. Keywords: alcohol use, adolescents, gender difference, mental health, depression, anxiety, self-esteem Í þessari rannsókn er áfengisneysla og geðheilsa íslenskra framhaldsskólanema skoðuð. Einnig er samband kynjamuns í tengslum við áfengisneyslu og geðheilsu ungmenna skoðað. Fyrri rannsóknir á áfengisneyslu og kynjamun sýna ólíkar niðurstöður. Þar sem sumar rannsóknir sýna að áfengisneysla unglingsdrengja sé meiri en stúlkna, sýna aðrar öfugar niðurstöður. Hvað kynjamun varðar þegar kemur að áfengisneyslu og geðheilsu hafa fyrri rannsóknir sýnt að unglingsstúlkur greini frá verri geðheilsu en drengir. Í þessari rannsókn voru gögn úr könnuninni Ungt fólk frá árinu 2018 notuð. Á meðal þátttakenda voru 1001 drengir (50.6%), 962 stúlkur (48.6%) og 15 (0.8%) þátttakendur sem greindu ekki frá kyni ...